Differences in age-related distribution of CSF alpha-synuclein seeding and Alzheimer profiles between PD with and without GBA1 variants - Stefanie Lerche; Isabel Wurster; Benjamin Roeben; Milan Zimmermann; Marcello Rossi; Angela Mammana; Simone Baiardi; Ann‑Kathrin Hauser; Christian Deuschle; Claudia Schulte; Piero Parchi; Kathrin Brockmann (npj Parkinson's Disease)
Abstract We studied the age- and genetic-related prevalence of CSF alpha-Synuclein seeding and Alzheimer profiles in 188 samples from PD participants without GBA1 variants (PDwildtype) and in 129 samples from PD participants with GBA1 variants (PDGBA1). While Alzheimer profiles increased with age in PDwildtype, it was sparse in PDGBA1. Alpha-Synuclein profiles remained stable with age in both cohorts. In PDwildtype, combined alpha-Synuclein/Alzheimer profiles were associated with earlier onset of cognitive impairment.